Natural Dimension in Ecological Aesthetic of Riverside Landscape - M. Karam; R.F. Abbawi (Engineering and Technology Journal, 2017)
Due to the local conditions that prevailed in the riverside landscape, the landscapers should be aware of the natural role of the ecological aesthetic, which has its importance in attracting the attention of the community and directed it towards the ecological environment, and from the discussion we have the problem which is, “the absence of studies to clarify the natural dimension of riverside ecological landscape”. Thereby determining the target put forward is to provide a database for the designers of riverside landscape, and through theoretical studies emerged the importance of the natural dimension. Also, there are three ecological components emerged in to achieve this dimension, and the component are (patch, edge, path) in riverside, thus the research began to test the hypothesis through analysis of riverside projects, and the results confirmed what referred to the hypothesis. The study then moved to test what had been reached on the results of local development projects to the riverside of the Tigris River in Baghdad. In addition, the result called for providing a proposal and come up with a summary of recommendations on how to achieve natural dimension in ecological aesthetic of the Tigris riverside landscape.